Morphological study of damage evolution in woven-laminates subjected to high-velocity impact. Issue 24 (17th December 2019) - Gil-Alba, Raúl; Alonso, Luis; Navarro, Carlos; García-Castillo, Shirley K.
Abstract: The aim of this experimental work was to study the evolution of damage in woven E-glass fiber/polyester laminates of four different thicknesses. After being impacted, these plates were inspected by nondestructive inspection techniques: ultrasound by C-Scan and B-Scan and visual inspection in order to confirm the qualitative and quantitative results. The damage presented an opening cone shape towards the rear face of thin laminates. On the other hand, two different opening cones of delamination grew towards the front and rear faces after a certain thickness in thick laminates.